2019
DOI: 10.1037/cou0000346
|View full text |Cite
|
Sign up to set email alerts
|

The development and validation of the Emotional Cultivation Scale: An East Asian cultural perspective.

Abstract: Research on emotion regulation in East Asian children and adolescents is limited. One obstacle hindering the development of emotion regulation for East Asian children and adolescents is the lack of a culturally sensitive measure. To fill this gap, we have developed and validated the Emotional Cultivation Scale using samples of Taiwanese children and adolescents. In Study 1, an exploratory factor analysis (n ϭ 341) identified two factors: Cultivating Emotion Strategies and Understanding Emotion Connotations. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 38 publications
0
40
0
Order By: Relevance
“…For our emotion regulation group intervention, increasing psychological needs satisfaction and positive affect also aligns well with goals for emotion regulation for those children and adolescents who have emotional disturbance concerns. Wang et al (2019) reported that psychological needs satisfaction and positive affect were helpful for This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Positive Emotions and Positive Relationsmentioning
confidence: 99%
See 3 more Smart Citations
“…For our emotion regulation group intervention, increasing psychological needs satisfaction and positive affect also aligns well with goals for emotion regulation for those children and adolescents who have emotional disturbance concerns. Wang et al (2019) reported that psychological needs satisfaction and positive affect were helpful for This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Positive Emotions and Positive Relationsmentioning
confidence: 99%
“…Emotional Cultivation was measured by the Emotional Cultivation Scale (Wang et al, 2019). Emotional cultivation (Nine items) assesses belief reframing, awareness of emotion consequences, action control, and regulating emotions through culturally-appropriate strategies in the East Asian cultural context.…”
Section: Emotional Cultivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial item communalities ranged between .19 and .61, with 17 of the 31 items yielding communalities greater than 0.40. The following criteria were then used for item retention: (a) a factor loading greater than .45, and (b) cross-loadings on other factors not exceeding .30 (Brown, 2006; L.-f. Wang et al, 2019). Of the preliminary 31 items, 16 items met all the criteria.…”
Section: Resultsmentioning
confidence: 99%